Current Directions and Future Research Priorities of Customer Data Analysis - Mohammed M Mohammed; Nagi A. Mohamed; Ali A. Adam; Shazali S. Ahmed; Fakhreldeen A. Saeed (Journal of Information System and Informatics, 2020)
Customer analysis is receiving special attention from both researchers and professionals. The objective of this paper is to identify the trends of techniques used to address customer’s current problems and shed light on future research directions using a literature review. We reviewed the literature for the last five years. The findings revealed that customer purchase was the most popular technique used by the research community followed by customer satisfaction and visit wit. Whereas customer segmentation and customer churn were the least. However, the regression method was commonly used for predicting customer purchase and behavior. But, social media and big data are still in their early stages for customer analytics research.